Views of Mental Health Professionals on the Necessity and Effectiveness of Mobile Psychiatric Care Units for Patients in Greece - Dr., Despina Sikelianou (International Journal of Psychosocial Rehabilitation, 2014)
The aim of this research was to study the views of mental health professionals on the necessity and effectiveness of mobile psychiatric care units for patients in the community. The survey method was used for the implementation of this research, the aim of which was to produce quantitative and statistical results. The research process lasted one (1) month (March – April 2010) and took place in 5 Prefec- tures in our country (Achaia, Thessaloniki, Lasithi (Crete), Rhodes and Serres). According to the views of mental health professionals, the results of the research showed that: i) the professional role of mental heath professionals in the Mobile Mental Health Units is very important because it is clearer, thus leading to the cohesion of the therapeutic group, іі) the inability of the existing mental health ser- vices to monitor the mentally ill patients in the community regularly was the major reason for the immediate development of Mobile Mental Health Units, ііі) the most significant aim of the operation of Mobile Mental Health Units is to meet the needs of mentally ill patients residing in remote areas, and iv) the mental health professionals suggest that Mobile Mental Health Units should be made avail- able in all prefectures of our country.